Decision Support System Analysis of Productive Financing Using Analytical Hierarchy Process (AHP) Method (Case Study of Sharia Business Unit of Bank Sumut) - T. Wulan Arianti; Andri Soemitra; Wahyu Syarvina (LPPM UIKA Bogor, 2023)
This study aims to analyze and find out about the decision support system used to assist in analyzing potential productive financing customers using the Analytical Hierarchy Process (AHP) method in the Sharia Business Unit of Bank Sumut. The method that researchers use in this research is the descriptive qualitative method. Data collection was carried out through interviews with the financing division of the Sharia Business Unit of the Bank of North Sumatra and documentation. The data collected by the author of the analysis is descriptive analysis. The results found and obtained in this study are Decision Support Systems that can be used to assist in the process of analyzing data on prospective productive financing customers when applying for financing, namely by analyzing the 5C principles (Capital, Character, Capacity, Collateral, and Condition of the economy). The application of the AHP method to the Sharia Business Unit of Bank Sumut can provide the best solution in determining the feasibility of providing financing.